Back to Basics: Exploiting the Innate Physico‐chemical Characteristics of Nanomaterials for Biomedical Applications. (1st August 2014) - Tay, Chor Yong; Setyawati, Magdiel Inggrid; Xie, Jianping; Parak, Wolfgang J.; Leong, David Tai
<x xml:space="preserve">Abstract</x> In nanomedicine design, emphasis is centered on the engineered impacts of the nanomaterials (NMs). However, failure to understand the unintended effects of nanomaterials on the cell biology can affect the overall performance, approval, and adoption in the clinic. Much of these unintended effects arise from unique physico‐chemical properties of the NMs. This feature article discusses some of the key physico‐chemical parameters of NMs and highlights how they could cause unexpected and novel biological responses, with some insights into their underlying mechanisms.